2008
DOI: 10.1038/jcbfm.2008.45
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Modulates ERK1/2, PI3K/Akt, and p38MAPK Activation in the Brain of the Anoxia-Tolerant Turtle Trachemys Scripta

Abstract: The fate of cells under anoxic or ischemic stress is determined by intracellular signaling pathways including the mitogen-activated protein kinases (MAPKs) and phosphatidylinositol 3-kinase (PI3K/Akt), which affect downstream members of the apoptotic cascade. The freshwater turtle Trachemys scripta is extremely tolerant of anoxia, surviving up to 48 h at room temperature and for weeks at 31C in the complete absence of oxygen. We investigated the relationship between the neuroprotective purine adenosine, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(46 citation statements)
references
References 43 publications
(68 reference statements)
4
39
3
Order By: Relevance
“…AKT is also activated after ischemia-reperfusion injury in the heart (18) and brain (38), and blocking AKT abolishes the protective effect of ischemic preconditioning in the heart (17). Moreover, AKT seems to be transiently phosphorylated in the initial phase of anoxia in warm-acclimated turtles (37). The observed reduction in AKT phosphorylation during long-term anoxia in the crucian carp may seem counterintuitive given its role as an important survival kinase in ischemic mammalian systems.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…AKT is also activated after ischemia-reperfusion injury in the heart (18) and brain (38), and blocking AKT abolishes the protective effect of ischemic preconditioning in the heart (17). Moreover, AKT seems to be transiently phosphorylated in the initial phase of anoxia in warm-acclimated turtles (37). The observed reduction in AKT phosphorylation during long-term anoxia in the crucian carp may seem counterintuitive given its role as an important survival kinase in ischemic mammalian systems.…”
Section: Discussionmentioning
confidence: 96%
“…AKT is known to be activated after retinal injury in goldfish (29) and is phosphorylated in the frog (Rana perezi) liver during hypoxia (3). Interestingly, it was recently shown that the total level of AKT was increased in anoxic turtle (Trachemys scripta) brain, and the phosphorylation was higher and lower compared with normoxic control at 1 and 4 h of anoxia, respectively (37). AMPK has been shown to be phosphorylated in the liver of hypoxic frogs (Rana perezi), but not in the liver or skeletal muscle of anoxic wood frogs (Rana sylvatica) (51).…”
mentioning
confidence: 99%
“…Because the downregulation of energy pathways and protection against cell death and oxidative stress are hallmarks of anoxia tolerance, it is not surprising to find evidence of p53 activation in the turtle (Zhang et al, 2013). Interestingly, there is also cross-talk between p53 and the phosphoinositide 3-kinase-protein kinase B (PI3K/AKT) pathway (Ladelfa et al, 2011), which is upregulated in the anoxic turtle brain (Milton et al, 2008;Nayak et al, 2011).…”
Section: Neuroprotection At the Molecular Levelmentioning
confidence: 99%
“…Activated PI3K/AKT and extracellular regulated kinase (ERK1/2), generally considered to be cytoprotective, increase in turtle neurons in vivo (Milton et al, 2008) and in vitro (Nayak et al, 2011), as does Bcl-2. AKT is thought to work in part through interactions with the Bcl-2 family of proteins (Wang et al, 2007), and as with other components of anoxic survival, these pathways are linked to increases in adenosine.…”
Section: Neuroprotection At the Molecular Levelmentioning
confidence: 99%
“…Both proapoptotic pathways (JNK and p38MAPK) and ostensible survival pathways (ERK and AKT) are activated simultaneously in response to cellular stress in mammalian cells [32]. The turtle brain, however, again shows a robust protective response; ERK and AKT are strongly upregulated in the anoxic brain, but with a marked suppression of p38MAPK [64]. In mammalian models, DOR-mediated HPC protection has also been related to increases in ERK and Bcl-2 activity, thus counteracting detrimental hypoxic increases in p38MAPK activity and cytochrome C release [65,66].…”
Section: Anoxia Tolerance and Ischemic Pc Share Common Mechanismsmentioning
confidence: 99%